Nanoencapsulation Boosts the Copper-Induced Defense Responses of a Susceptible Coffea arabica Cultivar against Hemileia vastatrix - Diego G. Gomes; Karina Sanada; Joana C. Pieretti; Luciana H. Shigueoka; Gustavo H. Sera; Amedea B. Seabra; Halley C. Oliveira (MDPI AG, 2023)
Due to the environmental risks of conventional Cu-based fungicides, Cu-loaded chitosan nanoparticles have been developed as nano-pesticides, aiming to protect plants against different diseases. In this sense, the objective was to verify the effects of chitosan nanoparticles containing Cu2+ ions on leaf discs of Coffea arabica cv. IPR 100 infected with Hemileia vastatrix. The treatments were water as a control (CONT), unloaded chitosan nanoparticles (NP), chitosan nanoparticles containing Cu2+ ions (NPCu), and free Cu2+ ions (Cu). Different concentrations of NP (0.25; 0.5; 1 g L−1) and Cu2+ ions (1.25; 2.5; 5 mmol L−1) were tested. The severity of the coffee rust was 42% in the CONT treatment, 22% in NP, and 2% in NPCu and Cu. The treatments protected coffee leaves; however, NPCu stood out for initial stress reduction, decreasing Cu phytotoxicity, promoting photosynthetic activity maintenance, and increasing antioxidant responses, conferring significant protection against coffee rust. At low concentrations (1.25 mmol L−1), NPCu showed higher bioactivity than Cu. These results suggest that Cu-loaded chitosan nanoparticles can induce a more significant plant defense response to the infection of Hemileia vastatrix than conventional Cu, avoiding the toxic effects of high Cu concentrations. Thus, this nanomaterial has great potential to be used as nano-pesticides for disease management.